The problem of the 1-center in graphs: Variations and applications in the resizing of electric energy - Nascimento, Isis Paulo do; Queiroz, Aquiles Braga de; Vera-Tudela, Carlos Andrés Reyna (Seven Editora, 2023)
Localization problems have applications in several areas, including the study of the planning of power distribution networks. In the present work, we present the problem of the modified 1-center in trees with applications to the study of the resizing of energy networks, as well as an algorithm for the resolution of the problem in time O( n log n), where we consider positive weights and distances. The work also includes the presentation of computational results for some of the methods presented, as well as new strategies for the application of localization problems to the design of power distribution networks. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-159